2009
DOI: 10.1109/tmtt.2009.2029958
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Communication for Implantable and Wearable Systems

Abstract: This paper presents the feasibility of applying an ultra-wideband (UWB) wireless scheme to both high data rate implantable neural recording and low data rate wearable biomedical applications. An extensive analysis on the UWB signal generation for biomedical application is discussed. A CMOS UWB transmitter has been designed, fabricated, and used in a high data rate neural recording system. A method to readily assemble a flexible UWB transmitter for wearable physiological monitoring system is also presented. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 15 publications
0
45
0
1
Order By: Relevance
“…Computer simulations of in-body to on-body (IB2OB) communications, i.e., a wireless link between a sensor operating inside the human body and an on-body gateway device, have suggested that data rates as high as 100 Mbit/s are feasible using UWB [10], [11]. Nevertheless, an in-vivo experiment on a living porcine subject demonstrated a significantly lower data rate of 1 Mbit/s and a bit error rate (BER) of 10 −2 for an UWB link between a transmitter implanted at a maximal depth of 12 cm into the abdominal cavity and an on-body receiver [12].…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations of in-body to on-body (IB2OB) communications, i.e., a wireless link between a sensor operating inside the human body and an on-body gateway device, have suggested that data rates as high as 100 Mbit/s are feasible using UWB [10], [11]. Nevertheless, an in-vivo experiment on a living porcine subject demonstrated a significantly lower data rate of 1 Mbit/s and a bit error rate (BER) of 10 −2 for an UWB link between a transmitter implanted at a maximal depth of 12 cm into the abdominal cavity and an on-body receiver [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways in which this can be accomplished is through the use of ultra-wide band (UWB) technology. Advantages of UWB technology include very high bandwidths (important for high-resolution image transmission from within the GI tract), low-power operation and the ability to accomplish high-accuracy ranging in challenging environments (Yuce et al, 2009;Chavez and Balasingham, 2013). Therefore, we focus on range-based localization using UWB signals in this paper.…”
Section: Figure 1 General Overview Of a Wireless Capsule Endoscopy Smentioning
confidence: 99%
“…Since the average FCC PSD emission limit for on-body UWB transmissions is −41.3 dBm/MHz [22], the maximum average transmit power P ave is −14.3 dBm. With the duty cycle T w /T f , P o max = P ave * T f /T w = 4 dBm [23]. For the in-body transmissions, we set P i max ≤ 10 dBm considering the emission limit and safety inside the human body [23].…”
Section: Simulationmentioning
confidence: 99%
“…With the duty cycle T w /T f , P o max = P ave * T f /T w = 4 dBm [23]. For the in-body transmissions, we set P i max ≤ 10 dBm considering the emission limit and safety inside the human body [23]. According to the scale of the human …”
Section: Simulationmentioning
confidence: 99%